Impact of professional education on the development of the staff potential in a modern library - Irina Fomenko; Irina Zamanova; Svetlana Ryadnova (Revista on line de Política e Gestão Educacional)
The article examines the need for professional education in the choice of the future profession, as well as the role of staff potential diagnostics in the work of a modern library, and the prospects and tasks in this sphere. The authors perform diagnostics of employees without special library education in municipal libraries of the Belgorod region, Russia. The study concludes that it is vital for library employees to get specialized education in librarianship in addition to that which they already have. In addition, libraries are advised to have a set of methods for diagnosing the potential of their staff with descriptions of these methods and options for their use.